THE USE OF PHONETIC METHOD IN TEACHING ENGLISH IN SDN 3 SUNGAI PINYUH - Irma Manda Negara (STBA Pontianak, 2016)
The purpose of this study is to improve student learning outcomes through the implementation of a phonetic method of memorizing vocabulary in teaching English to fifth grade students of SDN 3 Sungai Pinyuh. The subjects in this study are 22 students who are in the fifth grade in the academic year 2016 - 2017. Furthermore, the object of this study is the implementation of phonetic methods to improve learning outcomes of English. The steps that the author did was creating action planning, action, observation and reflection. This research is a form of class action research. The research instrument consists of observation, testing, and documentation. The successful implementation of a phonetic method on subjects known by their English learning outcome of prior actions, cycle I and cycle II.